Recombinant lectins : an array of tailor-made glycan-interaction biosynthetic tools - Oliveira, Carla Cristina Marques de (2013)
Lectins are a heterogeneous group of proteins found in plants, animals and microorganisms, which possess at least one non-catalytic domain that binds reversibly to specific mono- or oligosaccharides. The range of lectins and respective biological activities is unsurprising given the immense diversity and complexity of glycan structures and the multiple modes of interaction with proteins. Recombinant DNA technology has been traditionally used for cloning and characterizing newly discovered lectins. It has also been employed as a means of producing pure and sequence-defined lectins for different biotechnological applications. This review focuses on the production of recombinant lectins in heterologous organisms, and highlighting the Escherichia coli and Pichia pastoris expression systems, which are the most employed. The choice of expression host depends on the lectin. Non-glycosylated recombinant lectins are produced in E. coli and post-translational modified recombinant lectins are produced in eukaryotic organisms, namely P. pastoris and non-microbial hosts such as mammalian cells. Emphasis is given to the applications of the recombinant lectins especially (a) in cancer diagnosis and/or therapeutics, (b) as anti-microbial, anti-viral, and anti-insect molecules or (c) in microarrays for glycome profiling. Most reported applications are from recombinant plant lectins. These applications benefit from the tailor-made design associated with recombinant production and will aid in unraveling the complex biological mechanisms of glycan-interactions, bringing recombinant lectins to the forefront of glycobiology. In conclusion, recombinant lectins are developing into valuable biosynthetic tools for biomedical research.